2022
DOI: 10.1002/jez.2583
|View full text |Cite
|
Sign up to set email alerts
|

Age structure and growth pattern of a high‐altitude lizard population based on age determination by skeletochronology

Abstract: Age determination provides crucial data regarding the life history of a species.Skeletochronology is considered to be a reliable method for age determination but is seldom applied to the genus Phrynocephalus (Agamidae) as it requires careful bone histological analysis to determine the formation of the lines of arrested growth (LAGs). We analyzed LAGs in different bones of Phrynocephalus vlangalii, a small, high-altitude lizard, and demonstrated that the phalanges are the best materials for skeletochronology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(93 reference statements)
0
5
0
3
Order By: Relevance
“…Numerous research on reptile species found a favorable link between age and SVL (Altunıs ¸ık et al, 2022b;Ma et al, 2022;Piantoni et al, 2006;Yıldırım et al, 2019). But not all species exhibit this positive link (Odabas ¸et al, 2019), and in some, the correlation may differ based on sex (Cabezas-Cartes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous research on reptile species found a favorable link between age and SVL (Altunıs ¸ık et al, 2022b;Ma et al, 2022;Piantoni et al, 2006;Yıldırım et al, 2019). But not all species exhibit this positive link (Odabas ¸et al, 2019), and in some, the correlation may differ based on sex (Cabezas-Cartes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic and intrinsic variables can influence life history features as growth rate, fertility, age at maturity, and lifespan, with natural selection acting on phenotypes (Zamudio et al, 2016). For instance, habitat quality and ecological circumstances have a direct impact on a number of demographic factors, including longevity, fertility, and age structure (Altunıs ¸ık, 2018;Altunıs ¸ık et al, 2022aAltunıs ¸ık et al, , 2022bAtkins et al, 2020;Ma et al, 2022). For many species, determining an animal's age is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В этом случае альтернативой трубчатым костям конечностей для изучения возраста могут являться поперечные срезы позвонков. У большинства изученных видов в этих костях образуются линии задержанного роста, соответствующие диапаузам Ma et al, 2022), что было доказано экспериментально в неволе на нескольких видах подвязочных змей (Thamnophis sp.) .…”
unclassified
“…Стоит, однако, отметить, что использование позвонков, как регистрирующих структур, имеет свои недостатки: подготовка препаратов из них более трудоемка, первые линии задержанного роста могут быть резорбированы из-за ремоделирований костной ткани. Также не у всех особей удается однозначно отличить зимовочные линии от дополнительных, что может приводить к недооценке или переоценке возраста Ma et al, 2022). В связи с этим подобные исследования не получили широкого распространения или применяются на очень небольших выборках.…”
unclassified